Smoking and attitudes towards its cessation among native and international dental students in Lithuania - Apolinaras Zaborskis; Aiste Volkyte; Julija Narbutaite; Jorma I. Virtanen (BMC, 2017)
Abstract Background Dental professionals are uniquely positioned to discourage smoking among their patients. However, little is known about the role of cultural background and attitudes towards smoking in the education of these professionals. Our study aimed to compare native Lithuanian and international dental students' smoking habits, knowledge about the harmfulness of smoking and attitudes towards smoking cessation. Methods We conducted a cross-sectional survey of smoking and its cessation among dental students at the Lithuanian University of Health Sciences (Kaunas, Lithuania) in 2012. All Lithuanian and international dental students in each year of dental school were invited to participate in the survey during a compulsory practical class or seminar. Altogether 606 students participated in the survey with a response rate of 84.2%. Explanatory factorial analysis (EFA), multivariate Discriminant Analysis (DA) and Binary Logistic Regression (BLR) served for the statistical analyses. Results The percentages of occasional/current regular smokers were 41.1% and 55.7% (p = 0.068) among Lithuanian and international male students, and 22.7% and 22.9% (p = 0.776) among Lithuanian and international female students, respectively. The international dental students had a deeper knowledge of the harmfulness/addictiveness of smoking and held more positive attitudes towards smoking cessation among their patients than did the native Lithuanian dental students. Conclusions The findings of the study underscored the need to properly incorporate tobacco cessation training into the curriculum of dental education. However, consideration of the cultural background of dental students in building up their capacity and competence for intervening against smoking is essential.